Clinical significance of high-sensitivity C- reactive protein in systemic sclerosis - T. A. Nevskaya; A. A. Novikov; E. N. Alexandrova; E. S. Mach; M. E. Zapryagaeva; A. I. Speransky; N. G. Guseva; L. P. Ananjeva (Научно-практическая ревматология)
Objective. To determine diagnostic and prognostic significance of high-sensitivity Creactive protein (hsCRP) in systemic sclerosis (SS), to define relationship of this factor with activity of the disease and cardiovascular pathology, to assess role of pro-inflammatory cytokines in induction of acute phase proteins synthesis in SS.Material and methods. Serum levels of hsCRP, interleukin (IL) 6, IL 1β, IL1ra, IL 10, sIL2r were evaluated by enzyme immunoassay (EIA) in 40 pts with SS and 24 subjects of control group. Relationship with clinical features of the disease, endothelial dysfunction, capillaries structure changes, sub-clinical atherosclerosis, total coronary risk and some traditional cardiovascular risk factors was analyzed. Instrumental assessment included nailfold capillaroscopy, sonographic duplex examination of carotids , brachial arte ry sonographic examination. HsCRP prognostic significance was assessed in 51 pts with SS.Results. Elevated levels of hsCRP were found in 32% of SS pts and correlated with activity and severity of the disease, HAQ and SHAQ. Direct correlation of hsCRP with skin fibrosis distribution, interstitial lung disease, arthritis, laboratory indices of SS activity (ESR, sIL2r) and Scl-70 was revealed. HsCRP concentration in SS did not depend on character and intensity of cardiovascular pathology, subclinical atherosclerosis, endothelial dysfunction and proinflammatory cytokines production.Conclusion. HsCRP in SS reflects intensity of immuno-inflammatory process, correlates with T-cell activation markers and can be used as index of the disease activity, severity of skin and lung fibrosis.